تحديد المستويات المعيارية الخاصة بانتقاء الفرق المدرسية لكرة السلة ضمن مرحلة التعليم المتوسط - طبيب عبد الحفيظ (My University, 2023)
.......................................................................................absract................................................................. Study Title: Determining the standard levels for the selection of school basketball teams in the middle education stage. "A field study on a sample of middle school students (13-14) years old males of the state of Souk Ahras Objective of the study: - Setting standard levels in a controlled and scientific way to test students in the basic skills of basketball with the development of a scoring scale and its adoption in the calendar as a level statement to guide the intermediate stage. - Identify the effect of height and weight on the standard levels of selection of basic skills in basketball through the technical path. - Drawing the attention of educators, teachers and specialists to find the correct and codified scientific selection and the high levels it can achieve in the future through standard levels, which can be proposed to professors and researchers as a guide to help them in the field and future studies and similar team sports (handball, volleyball). . . . Study Tools: "Technical Path of Basketball Basic Skills in the Mediterranean". The main results of the study reached: - Standard levels of skill abilities have been determined for the smallest basketball in the phase of the wilaya of Souk Ahras have been determined. - It was found that weight has a weak negative impact on the results of students in the technical course of selection within the sport of basketball for school sports. - It was found that height has a very low positive effect on the results of students in the technical course of selection within the sport of basketball for school sports. Suggestions and recommendations: - Adopting the results of the standard levels presented and applying them in the selection of school basketball teams in scientific and more effective ways. - Apply these studies to the largest sample in the state and generalize the selection method to primary and secondary schools. - Coordination between inspectors of physical education and sports and university doctors in sports specialization to erase the gap and exploit academic studies and their real application in the field through the participation of professors of the subject. - Create field visits between schools and sports clubs to motivate, influence and spread the sports culture of basketball in the state. -Create units for evaluating and monitoring school sports activities and activate the activities of school sports associations. - Achieve new standard levels with different indicators and disciplines (handball and volleyball) for other age groups on which school sports depend in the state. -To propose the distribution of unified standard levels for all group and individual games across the state so that teachers can follow the selection in a scientific way and know the abilities of the students to lead them in the disciplines in which the teacher sees the possibility of achieving results in them. ......................................................................................الملخص........................................................ عنوان الدراسة: تحديد المستويات المعيارية الخاصة بانتقاء الفرق المدرسية لكرة السلة في مرحلة التعليم المتوسط "دراسة ميدانية على عينة من تلاميذ المرحلة المتوسطة (13-14) سنة ذكور لولاية سوق أهراس" هدف الدراسة: - وضع مستويات معيارية بطريقة مضبوطة وعلمية لاختبار للتلاميذ في المهارات الأساسية لكرة السلة مع وضع سلم تنقيط واعتماده في التقويم ككشف مستوى يهتدى به الطور المتوسط. - التعرف على تأثير الطول والوزن على المستويات المعيارية الخاصة بالانتقاء المهارات الأساسية في كرة السلة من خلال المسلك الفني. - لفت انتباه المربين والمدرسين وأهل الاختصاص بإيجاد الانتقاء العلمي السليم والمقنن وما يمكن أن يحققه من مستويات عالية في المستقبل من خلال المستويات المعيارية ما يمكن تقديم اقتراح للأساتذة والباحثين كدليل يعينهم في الميدان والدراسات المستقبلية والرياضات الجماعية المشابهة (كرة اليد، كرة الطائرة). ... أدوات الدراسة: "المسلك الفني الخاص بمهارات الأساسية لكرة السلة في المتوسط". أهم نتائج الدراسة المتوصل اليها: - تم تحديد المستويات المعيارية للقدرات المهارية لأصاغر كرة السلة في الطور المتوسط لولاية سوق اهراس. - تبين ان الوزن يؤثر تأثير سلبي ضعيف على نتائج التلاميذ في المسلك الفني الخاص بالانتقاء ضمن رياضة كرة السلة للرياضة المدرسية. - تبين أن الطول يؤثر تأثير إيجابي ضعيف جدا على نتائج التلاميذ في المسلك الفني الخاص بالانتقاء ضمن رياضة كرة السلة للرياضة المدرسية. الاقتراحات والتوصيات: - اعتماد نتائج المستويات المعيارية المقدمة وتطبيقها في انتقاء الفرق المدرسية لكرة السلة بطرق علمية وأكثر فاعلية. - تطبيق هذه الدراسات على أكبر عينة في الولاية وتعميم كيفية الانتقاء على المدارس الابتدائية والثانوية. - التنسيق بين السادة المفتشين لمادة التربية البدنية والرياضية ودكاترة الجامعات في الاختصاص الرياضي لمحو الفجوة واستغلال الدراسات الاكاديمية والتطبيق الحقيقي لها في الميدان عن طريق مشاركة أساتذة المادة. - خلق زيارات ميدانية بين المدارس والنوادي الرياضية للتحفيز والتأثير ونشر الثقافة الرياضية لكرة السلة في الولاية. - خلق خلايا للتقييم والمتابعة للنشاطات الرياضة المدرسية وتفعيل نشاط الجمعيات الرياضية المدرسية. - اجراء مستويات معيارية جديدة بمؤشرات واختصاصات مختلفة (كرة اليد وكرة الطائرة) لمراحل عمرية أخرى تعتمد عليها الرياضة المدرسية في الولاية. - اقتراح توزيع مستويات معيارية موحدة لكل الألعاب الجماعية والفردية عبر الولاية حتى يتمكن الأساتذة من متابعة الانتقاء بشكل علمي ومعرفة قدرات التلاميذ لتوجيههم في الاختصاصات التي يرى الأستاذ إمكانية تحقيق نتائج فيها. .................................................................................résumé................................................................. - Détermination des niveaux standards pour la sélection des équipes scolaires de basket-ball au niveau de l'enseignement moyen. (Une étude de terrain sur un échantillon de collégiens (13-14) ans, garçons, dans l'état de Souk Ahras). But de l'étude: - Fixer des niveaux standard de manière contrôlée et scientifique pour tester les compétences de base du basket-ball, en fixant une échelle de notation et en l'adoptant dans l'évaluation comme un contrôle de niveau qui guide l'étape moyenne. - Identifier l'effet de la taille et du poids sur les niveaux standards de sélection des habiletés de base en basketball à travers le cours technique. - Attirer l'attention des éducateurs, des enseignants et des spécialistes sur la recherche d'une sélection scientifique solide et légalisée et sur ce qui peut être atteint en termes de niveaux élevés à l'avenir grâce aux niveaux normatifs. Que peut-on suggérer aux professeurs et chercheurs comme guide pour les aider dans le domaine, les études futures, et les sports collectifs similaires (handball, volleyball). … Outils d'étude: "Le cours technique des compétences de base du basket-ball en moyenne." Les conclusions les plus importantes de l'étude : - Les niveaux standard des capacités techniques des plus jeunes basketteurs du stade intermédiaire ont été déterminés dans l'État de Souk Ahras. - Il a été constaté que le poids a un faible effet négatif sur les résultats des élèves dans le parcours technique de sélection au sein du sport du basket-ball pour le sport scolaire. - Il a été constaté que la taille a un effet positif très faible sur les résultats des élèves au cours technique de sélection au sein du sport du basket-ball pour les sports scolaires. Suggestions et recommandations : -Adopter les résultats des niveaux standard présentés et les appliquer dans la sélection des équipes de basket-ball scolaires de manière scientifique et plus efficace. -Appliquer ces études au plus grand échantillon de l'État et généraliser la méthode de sélection aux écoles primaires et secondaires. - Coordination entre les inspecteurs de la matière d'éducation physique et sportive et les docteurs universitaires de la spécialité mathématique pour combler le vide et valoriser les études académiques et l'application réelle de celles-ci sur le terrain à travers la participation des enseignants de la matière. -Créer des visites sur le terrain entre les écoles et les clubs sportifs pour motiver, influencer et diffuser la culture sportive du basket-ball dans l'État. - Créer des cellules d'évaluation et de suivi des activités sportives scolaires et activer les activités des associations sportives scolaires. - Réaliser de nouveaux niveaux standard avec différents indicateurs et disciplines (handball et volley-ball) pour d'autres tranches d'âge dont dépendent les sports scolaires dans l'État. -Proposer la distribution de niveaux standard unifiés pour tous les jeux de groupe et individuels à travers l'État afin que les enseignants puissent suivre la sélection de manière scientifique et connaître les capacités des étudiants à les diriger dans les disciplines dans lesquelles le professeur voit la possibilité d'atteindre résultats en eux.
دراسة ميدانية على عينة من تلاميذ المرحلة المتوسطة ( 13 - 14 )سنة ذكور لولاية سوق أهراس